Estetika Keberlanjutan: Analisis Semiotika pada Konten "Zero Waste Life" di Kanal YouTube NHK World-Japan - Lilik Murdiyanto (Jurnal Sosial Humaniora dan Pendidikan, 2025)
The global ecological crisis is often narrated through the rhetoric of disaster and fear for audiences. This often appears through various media consumed by the public. On the other hand, digital media offers an alternative space in the context of environmental communication based on aesthetics and lifestyle. This study aims to analyze the construction of the meaning of sustainability in the video series "Zero Waste Life" produced by NHK World-Japan. This study uses a qualitative approach. The analysis technique in this study uses Charles Sanders Peirce's semiotics. The results of this study found that various visual and narrative signs operate in a triadic logic. These signs change the ontological status of "waste" to "aesthetic resources" that can be utilized to reduce plastic waste. In addition, NHK World-Japan also narrates efforts to reduce plastic waste at the family level. This environmental narrative about reducing plastic waste is demonstrated through Japanese cultural philosophies, such as Mottainai (regret for waste), Wabi-Sabi (appreciation of imperfection), and Satoyama (harmony of the landscape) as rhetorical arguments in visual form. The video “Zero Waste life” triggers the emergence of an ethic of care to encourage audience awareness towards sustainable behavioral practices.